Respon Pertumbuhan dan Produksi Sawi Hijau Terhadap Pemberian Pupuk Organik Kascing - Berlian Limbong; Lollie Agustina P. Putri; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2014)
The aimed of this reaserch was to determine the respon of growth and production of mustard(Brassica rapa L.) on the application of organic fertilizers. The research was conducted on the farmfield with ± 25 meters above sea level from Mei to June 2013. Randomized Block Design was usedwith 2 factors, ie: varieties (Green Pakchoy and White Pakchoy) and organic fertilizers (0, 200, 300,400, 500 (g/polybag). The parameters observed were plant height, The number of leaf, leaf area, thebiomass weight of plant, the fresh weight of selling and the harvest index.The result of theobservations showed that varieties have significantly affected of plant height and the number ofleaf. while the organik fertilizer give significant effect to all of the parameters observed.Key word : mustard, variety, organic fertilizers